Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I had some problems with a certain exercise, came up with a solution, but I'm not sure it is correct.

Exercise ("MURPHY, C*-Algebras and Operator Theory", Chapter 2, exercise 1) Let $A$ be a Banach algebra such that for all $a\in A$, the implication $$Aa=0\text{ or }aA=0\Rightarrow a=0\qquad (1)$$ holds. Let $L,R$ be linear mappings from $A$ to itself such that for all $a,b\in A$, $$L(ab)=L(a)b,\quad R(ab)=aR(b),\qquad (2)$$ $$\text{and } R(a)b=aL(b).\qquad (3)$$ Show that $L$ and $R$ are necessarily continuous.

A double centralizer in a Banach algebra is defined to be a pair $(L,R)$ of bounded linear maps from $A$ to itself satisfying conditions (2) and (3). This exercise shows that if the Banach algebra satisfies condition (1) (for example, if it is a C*-algebra), then boundedness is consequence of (2) and (3).

I spent quite some time trying to solve this. Then,

Solution: By the Closed Graph Theorem, to show that $L$ is continuous, it suffices to show that for every sequence $\left\{x_n\right\}\subseteq A$ such that $x_n\rightarrow 0$ and such that $\left\{L(x_n)\right\}$ also converges, then $\lim L(x_n)=0$.

Let $x_n\rightarrow 0$ and $L(x_n)\rightarrow y$ in $A$. Then for every $n\in\mathbb{N}$ and for every $b\in A$, $$bL(x_n)=R(b)x_n,\quad\text{ by (3)}.$$ Taking $n\rightarrow\infty$, we have, for every $b\in A$, $$by=R(b)0=0,$$ that is, $Ay=0$. By (1), this implies that $y=0$.

Continuity of $R$ is proved similarly. Q.E.D.

Now, the problem is that I didn't use condition (2), and that seems too strong. Is there any problem with my reasoning? Thank you.

EDIT (see Martin's answer): I just found out that (1) and (3) imply (2). This explains why (2) was not used above. Let's show this:

Suppose $A$ is an algebra (not necessarily normed) satisfying (1) and let $L,R$ be linear maps from $A$ to $A$ satisfying (3).

Let $a,b\in A$. Then for every $c\in A$, $$c(L(ab)-L(a)b)=cL(ab)-cL(a)b\overset{(3)}{=}R(c)(ab)-(R(c)a)b=R(c)ab-R(c)ab=0.$$ Then $A(L(ab)-L(a)b)=0$, hence, by (1), $L(ab)=L(a)b$, for every $a,b\in A$. Similarly, $R(ab)=aR(b)$ for every $a,b\in A$. Therefore, (2) holds.

share|improve this question
1  
+1. Your argument is correct. You only need (3). –  1015 Dec 25 '13 at 18:05
add comment

1 Answer 1

up vote 2 down vote accepted

Your argument is correct. Note that (3) almost implies (2). Indeed, $$ cL(ab)=R(c)ab=cL(a)b. $$ So, if $A$ is unital or has a approximate identity, the implication holds.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.